Associação entre variáveis clínico-nutricionais e úlceras por pressão em idosos residentes em instituições de longa permanência - Gouveia, Léa Cristina (Universidade do Vale do Rio dos Sinos, 2021)
Pressure ulcers (UPP) are described as lesions located on the skin and or on the underlying tissue, usually on a bony prominence, resulting from pressure or from the combination of pressure and shear. The applied force affects cellular metabolism, reducing or obstructing the circulation of tissues, resulting in ischemia in this region (EUROPEAN PRESSURE ULCER ADVISORY PANEL - EPUAP, 2014 and EUROPEAN PRESSURE ULCER ADVISORY PANEL - NPUAP, 2014). It commonly develops in individuals who are unable to move due to illness or old age. However, it can be influenced by other factors, such as microclimate, soft tissue perfusion conditions (reduced tissue tolerance), presence of comorbidities (degenerative diseases, urinary or fecal incontinence) and nutritional status (malnutrition or obesity) (DE SOUSA, et al 2016). In addition, malnutrition, a common clinical feature in hospitalized patients, is a potentially important predisposition for the development of PU and delayed wound healing (SAGHALEINI, et al. 2018).
Keywords: Úlceras por pressão; Idosos; Clínico-nutricionais; Pressure ulcers; Seniors; Clinical nutritional; ACCNPQ::Ciências da Saúde::Nutrição